2016
DOI: 10.1016/j.baae.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Overabundant ungulates in French Sologne? Increasing red deer and wild boar pressure may not threaten woodland birds in mature forest stands

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 16254To link to this article : (M. Baltzinger).Allgemein hatte zunehmende Beweidungsintensität durch Rotwild keine negativen Effekte auf die Waldvögel dieser reifen Waldbestände mit einer entwickelten Kronenschicht und führte nicht zu einer geringeren Unterwuchsbedeckung. Die me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
7
0
3
Order By: Relevance
“…km −2 (range = 0.46-0.55: Richard et al, 2010), 0.96 ind. km −2 (0.69-1.23: Garel et al, 2010;Baltzinger et al, 2016), and 6.46 ind. km −2 (5-7.92: Lang et al, 2000;Baltzinger et al, 2016), respectively.…”
Section: Metric One: the Dispersal Potential (Dp)mentioning
confidence: 99%
See 1 more Smart Citation
“…km −2 (range = 0.46-0.55: Richard et al, 2010), 0.96 ind. km −2 (0.69-1.23: Garel et al, 2010;Baltzinger et al, 2016), and 6.46 ind. km −2 (5-7.92: Lang et al, 2000;Baltzinger et al, 2016), respectively.…”
Section: Metric One: the Dispersal Potential (Dp)mentioning
confidence: 99%
“…km −2 (0.69-1.23: Garel et al, 2010;Baltzinger et al, 2016), and 6.46 ind. km −2 (5-7.92: Lang et al, 2000;Baltzinger et al, 2016), respectively. Taking the mean seed recovery rates, and vector species density values, the DP of the dispersers can be ranked as: S. scrofa > C. elaphus > C. capreolus (DP scores: 284.89; 12.58; 2.86).…”
Section: Metric One: the Dispersal Potential (Dp)mentioning
confidence: 99%
“…Increasing ungulate populations are an issue for forest managers since the damages they may cause to trees and seedlings can jeopardize forest regeneration processes (Bradshaw & Waller, 2016). Many studies have been carried out under high densities of ungulate populations (Habeck & Schultz, 2015) obtained either experimentally (Bachand et al, 2014) or naturally (Martin, Stockton, Allombert, & Gaston, 2010), or resulting from local management choices (Baltzinger et al, 2016), or in areas where noticeable impacts had been a priori observed (Boulanger et al, 2015). The roles of ungulates as general drivers of changes in forest dynamics and biodiversity have been less investigated in standard conditions.…”
Section: Introductionmentioning
confidence: 99%
“…23 Cook-Patton et al 2014. 24 Baltzinger et al 2016;Cocquelet et al 2019. 25 Merceron et al 2004;Felton et al 2018.…”
Section: Faktori Kas Nosaka Briežu Dzimtas Dzīvnieku Barošanās Paradmentioning
confidence: 99%